The Relationship Between a Healthy Lifestyle and the Level of Physical Fitness of State Junior High School 1 Ujan Mas Students, Kepahiang Regency - Dyan Anggita Fitri; Yarmani; Tono Sugihartono (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
The purpose of this study is to ascertain how students' physical fitness levels at State Junior High School 1 Ujan Mas in Kepahiang Regency relate to leading a healthy lifestyle. Correlation analysis employing a quantitative approach and survey methodologies using instruments in the form of measurement tests, questionnaires for healthy lifestyles, and the TKJI test for physical fitness for individuals between the ages of 13 and 15 are the tools used in this sort of research. 336 students from the State 1 Ujan Mas Junior High School in Kepahiang Regency made up the study's population. In the meantime, 36 pupils were included in the sample process using a random sampling technique. The TKJI test and questionnaires were used to gather data. The precondition analysis test and correlation test were the methods of data analysis employed in this study. The study's findings indicate a connection between students' physical fitness levels at State Junior High School 1 Ujan Mas, Kepahiang Regency, and leading a healthy lifestyle. The decision to reject the null hypothesis (Ho) and accept the alternative hypothesis (Ha) was made because the value of rhitung 0.62 is greater than rtable in the product moment it was obtained 0.339. This means that there is a relationship between students at State Junior High School 1 Ujan Mas, Kepahiang district, and physical fitness.